2016
DOI: 10.1177/1090198116630527
|View full text |Cite
|
Sign up to set email alerts
|

Ideal Body Size as a Mediator for the Gender-Specific Association Between Socioeconomic Status and Body Mass Index

Abstract: Our study emphasizes the importance of gender and socioeconomic differences in BMI and ideal body size and suggests that public health interventions that promote perception of healthy weight could help mitigate SES-related disparities in BMI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 27 publications
0
14
0
Order By: Relevance
“…The quantitative evidence showed that increased SES (40,48,92) , non-manual occupations (92) and living in urban areas (27,63,69) were associated with slimmer body size preferences. Rural residency was associated with a greater preference for a larger body size, (27,63,69,116) whilst marriage was associated with a lower preference for a larger body size (8,78) .…”
Section: Socio-demographic Factorsmentioning
confidence: 99%
See 2 more Smart Citations
“…The quantitative evidence showed that increased SES (40,48,92) , non-manual occupations (92) and living in urban areas (27,63,69) were associated with slimmer body size preferences. Rural residency was associated with a greater preference for a larger body size, (27,63,69,116) whilst marriage was associated with a lower preference for a larger body size (8,78) .…”
Section: Socio-demographic Factorsmentioning
confidence: 99%
“…Younger participants had a greater preference for slimmer body sizes in Senegal (40) , Ghana (67,78) , Gambia (68) , South Africa (27) and the Seychelles (92) , but a greater preference for a larger body size in three studies conducted in Morocco (8,72,81) . Increased years of formal education was associated with a greater preference for both slimmer body size ideals in Ghana (48) , Cameroon (41) and Seychelles (92) and larger body size ideals in Morocco (8,81) . However, one study (78) in Ghana found that increased years of formal education was associated with a lower preference for larger body size but this was NS.…”
Section: Socio-demographic Factorsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, obesity was more frequent in men of higher SES, but among women of lower SES in Scotland (Heslop et al, ; Stringhini et al, ), a gender pattern also found in Seychelles (Stringhini et al, ). The social pattern in body mass index may partly relate to a gender‐specific perception of body size: In developing countries, a larger body size may be associated with health and affluence, and thinness with lack of resources and sickness (Stringhini et al, ; Yepes et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, leadership and capacity building (Airhihenbuwa et al, 2016), along with applying the theory of social gradient in health to understand the relationship between socioeconomic status and the risk for NCDs (Tenkorang & Kuuire, 2016), are among the innovations with which scholars and educators committed to improving conditions in the global south can draw to catalyze change. The articles on the global epidemiological transition by Atiim and Elliott (2016) and on the relationship of gender and socioeconomic status, body mass index, and perceptions of ideal body size by Yepes et al (2016) provide good examples of how epidemiologic assessment is being utilized to better plan a broad range of public health intervention approaches to improving health status. Two of the articles described research on new policy implementation strategies that can reduce the burden of NCDs.…”
mentioning
confidence: 99%